Bunga Mawar Sebagai Simbol Perilaku Manusia Menjadi Sumber Ide Dalam Seni Lukis - Udghitasari, Ni Made; Budiarta, I Dewa Putu Gede; Putra, I Gusti Ngurah (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
The purpose of the Final Project of Fine Arts Creation is a requirement for S1 graduation. This makes me want to metaphor the various types, shapes, and colors of roses as ideas for creating paintings in a naive style. Then perform various compositional processing, phenomena in life can be used as ideas in creating a work of painting, ideas or ideas cannot be separated from observations and interactions with surrounding conditions, as well as personal experiences. With the problem of how to express the technique, and the meaning of the various types and colors of roses into a painting. There are supporters in expressing techniques, and meanings, namely the theoretical basis as a reference for realizing paintings. So, my theoretical basis is to use aesthetic theory, semiotic theory to express the meaning of the rose metaphor, and naiveism to enrich the visuals of painting. The results of this creation are in the form of six works of art with the title: Breastfeeding Mother, Fighting Corona Virus, Self-Esteem, Rejecting Love, Relaxing, and Inhaling Taste. Through the writing that has been done, I can express the roses expressed in a naive style. Through this, a work can be created that will have a symbol or meaning.